Pengaruh Bermain Engklek Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun di TK Pembina HKBP Tarutung - Yesikha Sagala; Endang Junita Sinaga; Emmi Silvia Herlina; Ledyana Dwi Mei Situngkir; Adiani Hulu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The aim of this research is to determine the effect of playing crank on the gross motor development of children aged 5-6 years at the HKBP Tarutung Pembina Kindergarten. The research hypothesis is: "Engklek playing activities influence the gross motor development of children aged 5-6 years in the Tarutung HKBP Pembina Kindergarten". The population is children aged 5-6 years (group B) students at the Tarutung HKBP Pembina Kindergarten, namely 68 students. The research sample was determined using a purposive sampling technique, namely the Bintang class with 34 students as the experimental class and the Bulan class with 34 students as the control class. This research method is a quantitative research method with a quasi-experiment method (Quasi-experiment) with a Nonequivalent Control Group Design. The instrument used in this research was a 20-item questionnaire. Research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score). It was found that the average value for the experimental class was 0.7473 in the high category. And the average value for the control class is 0.1468, which is in the low category. From the results of the research carried out, an independent test was carried out using the t test and obtained a value of t = 12.727 > t table (α = 0.05; df = 66) = 2,000. Thus, it can be concluded that the research hypothesis (Ha) is accepted, namely that the activity of playing engklek influences the gross motor development of children aged 5-6 years at the HKBP Tarutung Pembina Kindergarten and H0 is rejected.